2021
DOI: 10.1002/chem.202102481
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylalanine Motif Drives Self‐Assembling in Hybrid PNA‐Peptide Conjugates

Abstract: Peptides and nucleic acids can self-assemble to give supramolecular structures that find application in different fields, ranging from the delivery of drugs to the obtainment of materials endowed with optical properties. Forces that stabilize the "suprastructures" typically are hydrogen bonds or aromatic interactions; in case of nucleic acids, Watson-Crick pairing drives self-assembly while, in case of peptides, backbone hydrogen bonds and interactions between aromatic side chains trigger the formation of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…It can be clearly seen that the morphology of the two supramolecular structures is completely different: 4Fat formed visible fibers, whereas the 4Fgc system did not exhibit homogeneous fibers and only small heterogeneous aggregates could be visualized (Figure 5). Morphology of 4Fgc is similar to that observed for FFgc [10] . The 4Fat fibers were arranged in an extended way having a broad distribution of width and length (Figures 5A, C, E and S8): most fibers are 400 nm long and show a width in the range 12–15 nm.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…It can be clearly seen that the morphology of the two supramolecular structures is completely different: 4Fat formed visible fibers, whereas the 4Fgc system did not exhibit homogeneous fibers and only small heterogeneous aggregates could be visualized (Figure 5). Morphology of 4Fgc is similar to that observed for FFgc [10] . The 4Fat fibers were arranged in an extended way having a broad distribution of width and length (Figures 5A, C, E and S8): most fibers are 400 nm long and show a width in the range 12–15 nm.…”
Section: Resultssupporting
confidence: 63%
“…The PNA heterodimer "gc" conjugated to FF produces mainly spheroids; indeed, samples are not homogeneous, as they contain aggregates of different shape and dimension. [10] Consistent with this observation is the lack of ordered structure in other FF conjugates, containing polyphenylalanine conjugated to the metal chelator DOTA. It was reported that the replacement of FF by 4F resulted in ordered aggregates, in which tetraphenylalanines were arranged in antiparallel beta sheets.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…29 While not found in Nature (except for the nucleoamino acid willardiine) and that their prebiotic role has been hypothesized, [45][46][47] nucleopeptides are mainly synthetic compounds developed for biological applications 47 thanks to their ability to interact with proteins or enzymes such as serum albumin 48 or the reverse-transcriptase of HIV. 49 Harnessing the abilities of peptides and nucleobases to self-assemble in specific conditions, several research groups reported on the use of nucleopeptides to study their self-organisation and to develop new properties and applications 29 such as tuneable or functional supramolecular architectures, [50][51][52][53] fluorescence, [54][55][56][57] to selectively sequestrate ATP in cells 58 or to deliver RNA into cells, 59 to name a few. In some instances and depending on both the design and the mode of preparation (i.e., the formulation), nucleopeptides are able to form lowmolecular weight gels, an emerging and promising approach to develop innovative soft materials.…”
Section: Nucleopeptide Self-assembliesmentioning
confidence: 99%